CONSUMER WILLINGNESS TO PAY FOR SUSTAINABLE PRODUCTS - Janice Carysa Siahaya; Tania Monica Potu; Yanuar Dananjaya (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
The growing awareness of sustainability among consumers in Indonesia has led to a significant shift in preferences towards more environmentally friendly products, particularly in the fashion industry. This shift has been particularly evident in the case of Sejauh Mata Memandang, a fashion brand committed to sustainability. However, despite the increasing awareness, there is limited research on how far consumers are willing to pay a premium for sustainable fashion products. This study aims to explore the factors that influence consumers' willingness to pay a premium price for sustainable fashion products, specifically focusing on Sejauh Mata Memandang. The factors examined include Environmental Awareness, Price, Product Quality, and Trendiness, with the goal of understanding how these elements contribute to Brand Image, and how Brand Image influences the willingness to pay a premium price. Using a quantitative approach, data was collected from 200 consumers who have purchased Sejauh Mata Memandang products. The findings reveal that Environmental Awareness, Price, and Product Quality have a significant effect on Brand Image, which, in turn, influences consumers' willingness to pay premium prices. However, Trendiness did not show a significant impact on Brand Image in the case of Sejauh Mata Memandang. This research contributes to the academic discussion on sustainable marketing and consumer behavior in emerging markets, offering valuable insights for brands and policymakers to develop more effective marketing strategies and sustainability-oriented policies.